Improving Poetry Writing Skills through the Suggestopedia Method with Song Media - Ayu Haryanti; Heny Subandiyah (Raja Zulkarnain Education Foundation, 2026)
This study aims to: (1) describe the learning process of poetry-writing skills through the Suggestopedia method using song media among students of class X TPM 1 at SMKN Negeri Kudu Jombang; (2) improve students’ poetry-writing skills through the application of the Suggestopedia method with song media in class X TPM 1 at SMKN Negeri Kudu Jombang; and (3) describe the responses of students in class X TPM 1 at SMKN Negeri Kudu Jombang after participating in poetry-writing instruction using the Suggestopedia method with song media. The research method employed was descriptive quantitative with a one-group pretest–posttest design. The research subjects consisted of 35 students who participated in poetry-writing instruction through the Suggestopedia method with song media. Data were collected through observation, poetry-writing tests, and student response questionnaires. The results indicate that the Suggestopedia method using song media significantly improved students’ poetry-writing skills. The average pretest score of 67.83 increased to 80.71 in the posttest, showing an improvement of 12.88%. This improvement occurred due to a relaxed learning atmosphere, the presence of positive suggestions from the teacher, and the role of music in stimulating students’ imagination and creative expression. Based on the questionnaire results, 93% of students provided positive responses to the implementation of this method, as it was considered enjoyable, motivating, and helpful in facilitating the expression of ideas into poetic form. Thus, the Suggestopedia method using song media can serve as an alternative and effective instructional strategy for improving poetry-writing skills while also strengthening students’ affective and creative aspects in Indonesian language and literature learning.